Partikel Dirac dalam Sumur Potensial Dinamis - Tiandho, Yuant (EduMatSains, 2016)
Infinite square well potential is one of the most elementary quantum mechanical system. The calculation of this case is not too complicated, however, it can show the differences between quantum world and classical world with clearly. In this letter, we expand the discussion about the infinite square well potential for dynamic potential wellÂ  by involving relativistic corrections. The dynamic potential is defined as potential wall that depend on time because the potential can moving with constant velocity. The Dirac equation is used to describe condition in the potential well. By this consideration, we hope the result will be useful in the development of nanoelectronic devices. To obtain solution of probability density of Dirac particles that depend on space and time, we transform the Dirac equation into hyperbolic coordinates and the differential equations can be solved by separation variables method.